Effects of Single and Blended Coating Pigments on the Inkjet Image Quality of Dye Sublimation Transfer Printed Paper: SiO2, CaCO3, Talc, and Sericite - Chi-Ching Lin; Fu-Ling Chang; Yuan-Shing Perng; Shih-Tsung Yu (Advances in Materials Science and Engineering)
In this study, we investigated the effects on the image quality of CaCO3, SiO2, talc, and sericite on coated inkjet paper. The papers serve as dye sublimation transfer paper for printing on fabrics. The brightness, smoothness, and contact angle of the coated papers were evaluated. The papers were then printed with a textile color image evaluation test form, and the imprinted images were evaluated with respect to six criteria of the solid ink density, tone value increase, print contrast, ink trapping, grayness, and hue error. The overall printed image quality was correlated with the smoothness and brightness of the coated paper but showed no correlation with the contact angle. For single-pigment-coated papers, CaCO3 produced paper with the best color difference performance and could be substituted for silica. On the other hand, SiO2 was found to be suitable for blending with talc, calcium carbonate, and sericite, and its combination with these materials generally produced better image qualities than silica alone. Talc and sericite, when blended with silica as composite coating pigments, produced better printed image qualities than those as single-pigment-coated papers. The overall image quality ranking suggests that the best performance was achieved with CaCO3-, SiO2/talc-, CaCO3/SiO2-, SiO2/sericite-, and SiO2-coated papers.